Development and psychometric properties of a measure of catheter burden with bladder drainage after pelvic reconstructive surgery. Issue 4 (26th July 2016) - Carpenter, Janet S.; Heit, Michael; Rand, Kevin L.
Abstract : Aims: Catheter burden after pelvic reconstructive surgery is an important patient‐reported quality of life outcome in research and clinical practice. However, existing tools focus on long‐term catheter users rather than short‐term postoperative patients. The study aim was to evaluate the psychometric properties of a modified version of the intermittent self‐catheterization questionnaire (ISC‐Q) in postoperative pelvic reconstructive patients. Methods: After experts convened to discuss and modify the ISC‐Q items based on their knowledge of women's experiences and clinical practices, 178 women (108 with transurethral and 70 with suprapubic catheters) completed the modified scale and other measures as part of a larger parent study designed to assess health‐related quality of life (HRQoL) following pelvic reconstructive surgery requiring bladder drainage. Results: During psychometric testing, the modified ISC‐Q was reduced to six items encompassing two factors: a three‐item difficulty of use factor and a 3‐item embarrassment factor. The new scale was named the short‐term catheter burden questionnaire (STCBQ). The two‐factor model was robust in both subsamples. Only scores within and not between subsamples can be meaningfully compared due to a lack of scalar invariance. Correlations among STCBQ total scores, subscores, and a single satisfaction item indicated good construct validity. Correlations with patient demographics provided further information about the scale. Conclusions: The STCBQ is a short, efficient assessment of short‐term catheter burden following pelvic reconstructive surgery. The scale can be used as an important patient reported outcome measure in clinical practice and research. Neurourol. Urodynam. 36:1140–1146, 2017 . © 2016 Wiley Periodicals, Inc.